Transforming community policing: mobilization, engagement, and collaboration - Russell, Hugh C. (Emond, 2023)
"Transforming Community Policing takes a different approach to community policing than that of its peers: it focuses on community collaboration and community-based problem solving, rather than police outreach and police-led problem solving. This type of community-based policing is seen by many as the future of policing."--